A critical and comprehensive review of the current status of 17β-estradiol hormone remediation through adsorption technology (2024)
Even at low concentrations, steroid hormones pose a significant threat to ecosystem health and are classified as micropollutants. Among these, 17β-estradiol (molecular formula: C18H24O2; pKa = 10.46; Log Kow = 4.01; solubility in water = 3.90 mg L−1 at 27 °C; molecular weight: 272.4 g mol−1) is extensively studied as an endocrine disruptor due to its release through natural pathways and widespread use in conventional medicine. 17β-estradiol (E2) is emitted by various sources, such as animal and human excretions, hospital and veterinary clinic effluents, and treatment plants. In aquatic biota, it can cause issues ranging from the feminization of males to inhibiting plant growth. This review aims to identify technologies for remediating E2 in water, revealing that materials like graphene oxides, nanocomposites, and carbonaceous materials are commonly used for adsorption. The pH of the medium, especially in acidic to neutral conditions, affects efficiency, and ambient temperature (298 K) supports the process. The Langmuir and Freundlich models aptly describe isothermal studies, with interactions being of a low-energy, physical nature. Adsorption faces limitations when other ions coexist in the solution. Hybrid treatments exhibit high removal efficiency. To mitigate global E2 pollution, establishing national and international standards with detailed guidelines for advanced treatment systems is crucial. Despite significant advancements in optimizing technologies by the scientific community, there remains a considerable gap in their societal application, primarily due to economic and sustainable factors. Therefore, further studies are necessary, including conducting batch experiments with these adsorbents for large-scale treatment along with economic analyses of the production process.